Optimal allocation of faculty time under uncertainty in production - Huang, Cliff J. (Economics of education review, 1981)
A model of expected utility maximization is used to study the optimal allocation of a professor's time between research and teaching in a situation where both production activities are subject to uncertainty. It was shown that, in general, a professor's optimal allocation of time under uncertain production departs from the certainty strategy. An explicit model was developed to evaluate the effects of time effort in research and teaching with respect to changes in the degree of uncertainty, the Pratt-Arrow index of risk aversion, and the unit output rewards of research and teaching (for example, “merit pay”).